Patterns and determinants of intra-industry trade in Southeast Asia: evidence from the automotive and electrical appliences sectors - Salim, Ruhul; Islam, A.; Bloch, Harry (World Scientific Publishing Company, 2015)
Using finely disaggregated data at six-digit harmonized code classification level, this paper examines the patterns and determinants of horizontal and vertical intra-industry trade in the automobile and electrical appliances sectors during the past few decades among the six major Southeast Asian countries. It is found from the analysis of the data that intra-industry trade is much higher than the inter-industry trade in each of these two sectors. Further, the determinants of these two types of trade are found to differ somewhat in terms of sign and magnitude across the sectors, implying the importance of sector-specific factors as influences on the pattern of trade.